Fostering China-ASEAN Relations Through E-Commerce Diplomacy: Lazada and Alibaba - Erika Intan Hulieta; Deasy Silvia Sari (TRANSBORDERS: International Relations Journal, 2026)
The evolution of the digital economy in the wake of economic globalization has become a focal point for nations worldwide, shaping socio-economic development and fostering cross-border collaboration. This paper delves into the multifaceted role of e-commerce platforms, particularly Alibaba and Lazada, in fostering relations between China and ASEAN countries within the context of the Belt and Road Initiative (BRI) and broader commercial diplomacy frameworks. Through a comprehensive literature review methodology, the study synthesizes theoretical frameworks from international relations and empirical evidence to elucidate the mechanisms driving cooperation between China and ASEAN nations in the realm of e-commerce. The findings underscore the pivotal role of digital infrastructure development, digital product manufacturing, and cross-border e-commerce facilitation in enhancing regional cooperation. China's strategic investments in ASEAN's digital infrastructure and manufacturing sector have catalyzed economic growth and deepened regional integration. Moreover, Alibaba's strategic acquisitions and partnerships, particularly with Lazada, have facilitated market expansion and strengthened China-ASEAN trade ties. The study also highlights the importance of policy coordination and institutional frameworks in fostering digital economy cooperation between China and ASEAN countries. Keywords: Alibaba; ASEAN-China Relations; E-Commerce; E-Commerce Diplomacy; Lazada